Environmental drivers of endemism in the Canary Islands: linking traits to island theory - Vanessa, Cutts (2022)
Islands have been very influential in the fields of ecology and evolution. They are frequently described as dynamic because species richness and evolution are especially sensitive to island geological processes, leading to high biodiversity and endemism, which fluctuate through space and time. Islands thus serve as natural laboratories with which to test theories about processes that alter biodiversity. Traditional approaches in island biogeography used species richness to assess island ecological and evolutionary patterns but there is now a movement towards the use of functional traits as they can provide more mechanistic insight. Functional trait ecology has greatly increased our understanding of biodiversity patterns on the mainland and more recent advances are using multiple traits to position species in multi-dimensional space, thus indicating their role in a community. The adoption of multi-trait approaches on islands is part of the growing field of functional island biogeography. The overarching aim of this thesis was to understand how the abiotic environment influences both the functional and geographical composition of plants endemic to islands (island endemics). This objective was investigated through a series of scientific papers, which are either published or under review, focussing on the flora of the Canary archipelago as a model system. Firstly, I investigated patterns of endemic richness along topographic gradients. Endemic species typically occur in higher proportions at high elevations and it is theorised that increasing isolation with elevation leads to higher speciation rates (per species). Chapter 4 (which follows Introduction, Literature Review and Methods chapters) investigates the links between topographic isolation and endemism. Here, I extend the theory of isolation by elevation to make predictions at a finer scale, focusing on the isolating influence of small-scale fluctuations in topography in the form of deep barrancos (ravines). I assessed how the depth of barrancos influenced the proportions of species in different endemism categories. Depth did not influence endemism, but elevation did: endemic species were present in higher proportions at lower elevations within the barrancos. This is opposite to what was expected but suggests that, although barranco depth as a measure of isolation did not influence endemism, the presence of barrancos in general plays a role in shaping patterns of endemism. Trait-based approaches in island biogeography are still in their very early stages because, as island endemics are typically rare on a global scale, trait data are often severely lacking. Chapter 5 addresses this issue by evaluating the quality of existing plant trait data that are available for Canary Island species in an open access database, as well as comparing recently collected plant trait data from field expeditions with trait data that have been digitised from the literature. The outcome of this revealed a severe lack of trait data for Canary Island native species and lack of overlap between trait data collated from open access databases and traits expressed by island endemics. However, on a more promising note, trait data digitised from the literature can accurately represent what is measured in the field. This means that not all future research may require intensive field expeditions, which can be costly, time-consuming and destructive. Classic approaches in island biogeography have a strong focus on species richness and the historical lack of functional trait data means that trait variation within and across islands is largely unknown. In Chapter 6, I explore the functional composition of island species and how this relates to island age. I use plant functional trait data to investigate the link between species traits and their environment through the lens of rarity. The rarity of species traits is investigated using the index ‘functional distinctiveness’, defined as the average distance in trait space from the focal species to all other species. Functional distinctiveness of endemic and non-endemic species is analysed with respect to their occupancy in climatically rare habitats. The main result of this analysis is that endemics have an affinity for rare habitats but they are not more distinct in their traits than non-endemic species. Furthermore, as islands increased in age, species occupied fewer rare climates but no change in functional distinctiveness occurred. In other words, I found no link between trait distinctiveness and occupancy of rare climates. There has been a recent call for the inclusion of functional traits into island research. This thesis endeavours to answer this call by incorporating functional traits into island theory. To summarise the main findings, topography and climate influence the distribution of endemic species on islands, but no clear signal in their traits could be found. Trait data for Canary Island species are still lacking but the viability of some other sources of trait data, besides field data, should be encouraging to future researchers.